Проникновение слабого магнитного поля в ВТСП керамику Bi-Pb-Sr-Ca-Cu-Fe-O - Э. А. Мугнецян; М. Т. Айвазян; Н. М. Добровольский; А. Г. Саркисян (ՀՀ ԳԱԱ հրատ.)
Экспериментально исследовано поведение керамического ВТСП Bi-Pb-Sr-Ca-Cu-Fe-O с джозефсоновской средой в интервале магнитных полей H = 0 ÷ 600 мЭ в условиях компенсации магнитного поля Земли. Փորձարարականորեն հետազոտված է Ջոզեֆսոնյան միջավայրով Bi-Pb-Sr-Ca-Cu-Fe-O կերամիկայի վարքը H = 0 ÷ 600 մէ մագնիսական դաշտերում, Երկրի մագնիսական դաշտի կոմպենսացման պայմաններում։ The behavior of ceramic HTSC Bi-Pb-Sr-Ca-Cu-Fe-O with the Josephson medium within the range of magnetic fields H = 0÷600 mOe under the conditions of the Earth’s magnetic field compensation is investigated experimentally.
Keywords: Physics; Science; Radiophysics